2000
DOI: 10.1016/s0896-6273(00)81168-x
|View full text |Cite
|
Sign up to set email alerts
|

rpm-1, A Conserved Neuronal Gene that Regulates Targeting and Synaptogenesis in C. elegans

Abstract: Little is known of mechanisms regulating presynaptic differentiation. We identified rpm-1 in a screen for mutants with defects in patterning of a presynaptic marker at certain interneuronal synapses. The predicted RPM-1 protein contains zinc binding, RCC1, and other conserved motifs. In rpm-1 mutants, mechanosensory neurons fail to accumulate tagged vesicles, retract synaptic branches, and ectopically extend axons. Some motor neurons branch and overgrow; others show altered synaptic organization. Expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
287
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 241 publications
(309 citation statements)
references
References 53 publications
20
287
2
Order By: Relevance
“…2-methyl-2- [methylthio]proprionaldehyde O- [methylcarbamoyl]oxime (aldicarb) was obtained from Chem Services, Inc. (West Chester, PA). Pharyngeal pumping and aldicarb sensitivity were tested as described previously , and snt-1(md290) represent null alleles based on molecular, genetic, and immunohistochemical criteria (Nonet et al, 1993Schaefer et al, 2000). ae x -3( y255) behaves as a strong loss-of-f unction allele (Iwasaki et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…2-methyl-2- [methylthio]proprionaldehyde O- [methylcarbamoyl]oxime (aldicarb) was obtained from Chem Services, Inc. (West Chester, PA). Pharyngeal pumping and aldicarb sensitivity were tested as described previously , and snt-1(md290) represent null alleles based on molecular, genetic, and immunohistochemical criteria (Nonet et al, 1993Schaefer et al, 2000). ae x -3( y255) behaves as a strong loss-of-f unction allele (Iwasaki et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, proteins of the presynaptic active zone are properly localized in unc-104 mutants. Specifically, liprin/ SYD-2 (Zhen and Jin, 1999), Rab-3 interacting molecule/ UNC-10 ( Koushika et al, 2001), and RPM-1 (Schaefer et al, 2000;Zhen et al, 2000) are correctly localized in the dorsal cord; however, these incomplete synapses cannot direct the clustering of GABA receptors. Therefore, sites of presynaptic differentiation can be specified in the motor neuron independently from the formation of synaptic vesicle aggregates.…”
Section: The Differentiation Of Gabaergic Neuromuscular Junctions Resmentioning
confidence: 99%
“…Synapse Formation-Previous studies have shown that rpm-1, fsn-1, and glo-4 loss-of-function (lf) mutants have defects in axon termination and synapse formation in the mechanosensory neurons of C. elegans (3,12). Furthermore, fsn-1 and glo-4 function in parallel genetic pathways to mediate the function of rpm-1 (12).…”
Section: Transgenic Expression Of Rip Inhibits Axon Termination Andmentioning
confidence: 99%
“…Studies in worms, flies, fish, and mice have identified roles for the PHR proteins in synapse formation (2)(3)(4)(5), axon guidance and extension (6 -11), and axon termination (3,(12)(13)(14).…”
mentioning
confidence: 99%